Treatment effects of the MARA appliance and Activator-Headgear combined with fixed appliances in Class II division 1 malocclusion patients: A retrospective longitudinal study - Deborah Brindeiro de Araújo BRITO; Silvio Augusto BELLINI-PEREIRA; Camilla Fiedler FONÇATTI; José Fernando Castanha HENRIQUES; Guilherme JANSON (Dental Press Editora, 2023)
ABSTRACT Introduction: Class II division 1 malocclusion treatment with functional devices offers acceptable results. These devices can be removable or fixed, and the essential difference between them is the need for compliance. It is clinically important to investigate if there are differences in the treatment effects of these devices that present different characteristics. Objective: This retrospective longitudinal study compared the treatment effects of Class II correction with the MARA appliance, Activator-Headgear (AcHg) combination, both followed by multibracket fixed appliances, and an untreated control group. Material and Methods: Each experimental group was composed of 18 patients, with a baseline mean age of 11.70 and 10.88 years, treated for 3.60 and 3.17 years. The control group consisted of 20 subjects with baseline mean age of 11.07 years. The groups were evaluated before (T1) and after (T2) treatment. Lateral radiographs were used to evaluate the treatment changes with treatment (T2-T1), compared to the control group. Intergroup comparisons were performed using repeated-measures analysis of variance (ANOVA), followed by Tukey's test. Results: The AcHg group showed significantly greater maxillary growth restriction than the MARA, while the mandibular changes were due to natural growth. Both devices promoted significantly greater maxillary incisors retrusion, mandibular incisors labial inclination, and improvement of overjet and molar relationships, compared to the control. Conclusions: Both functional devices followed by multibracket appliances were effective to correct Class II malocclusion. Nonetheless, the AcHg combination presents superior skeletal effects, due to significantly greater maxillary growth restriction compared to the MARA appliance. Moreover, the appliances presented similar dentoalveolar effects.